Analysis of Vulnerability and Effesctiveness of Strengthening Community Collaboration in Disaster Mitigation in Bukit Lawang Plantation Tourism Village, Bahorok District, Langkat Regency - Nainggolan, Hetty Claudia; Dalimunthe, Femmy Indriany; Prastia, Rudi; Simamora, Beatrice Jennifer; Sihite, Sasdotio Yen Marlina (LPPM Institut Pendidikan Nusantara Global, 2024)
Flooding is one of the unexpected natural phenomena that often occurs in all parts of Indonesia, one of which is in the tourist village of Bukit Lawang Plantation. Precisely on November 2, 2003, a flash flood occurred. Therefore, at this time the flood hazard in Bukit Lawang Plantation Village is clearly visible, it is necessary to know how vulnerable the flood danger is in Bahorok district, so that the community can anticipate and be vigilant if the flood disaster occurs again. This study aims to analyze the vulnerability and effectiveness of strengthening community collaboration in disaster mitigation in Bukit Lawang Plantation Village, Bahorok District, Langkat Regency. This area is one of the ecotourism destinations that is prone to flood disasters, especially flash floods that have occurred several times. The approach used in this study is a qualitative descriptive method with data collection through interviews, field observations, and documentation studies. This study identifies various factors that affect the level of vulnerability of communities to disasters, including physical, social, economic, and environmental vulnerabilities. The results of the study show that collaboration between the local community, the government, and related parties in disaster mitigation in Bukit Lawang Village has not been optimal. Despite several mitigation efforts such as riverbank elevation and disaster preparedness training, communities still face high risks due to a lack of effective coordination and engagement. In addition, community vulnerability is exacerbated by limited access to mitigation resources and a lack of understanding of disaster risk. This study recommends increasing more effective collaboration between local communities, governments, and the private sector through community-based mitigation programs, which involve disaster education, capacity building, and better infrastructure planning. Strengthening this collaboration is expected to increase community resilience to future disaster threats and support the sustainability of ecotourism in Bukit Lawang.